Strategi Marketing Public Relations dalam Meningkatkan Penghimpunan Dana Pada LAZISWAF UNIDA Gontor - Utomo, Bambang Setyo; Farhan, Muhammad Syahrul (Indonesian Social Science Review, 2024)
This study aims to determine the marketing public relations strategy of the Amil Zakat Infak Sedekah and Waqf Institution (LAZISWAF) UNIDA Gontor in increasing fundraising for 6 periods. This research uses a qualitative approach with a case study method. The results of this study indicate that LAZISWAF UNIDA Gontor has conducted marketing public relations in increasing fundraising from the theory of marketing public relations proposed by Thomas L. Harris that three ways strategy: push, pull and pass. Push strategy LAZISWAF UNIDA Gontor conducts door to door donations around student dormitories, jabi recycling around lecturers' homes, distributing one day one story posters to student groups via whatsapp and Instagram. Pull strategy LAZISWAF UNIDA Gontor does advertising in the form of bulletins and posters, as well as through billboards, and publishes on social media such us Instagram, Youtube, and websites. Pass strategy LAZISWAF UNIDA Gontor conducts social programs such as: Qur'an waqf, UNIDA cares about natural disasters, and Zakat and Waqf Studies. The implication of these findings suggests that a well-rounded marketing public relations strategy, combining push, pull, and pass approaches, can significantly enhance fundraising efforts over multiple periods.   Penelitian ini bertujuan untuk mengetahui strategi marketing public relations  Lembaga Amil Zakat Infak Sedekah dan Wakaf (LAZISWAF) UNIDA Gontor dalam meningkatkan penghimpunan dana selama 6 periode. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Hasil penelitian ini menunjukkan bahwa LAZISWAF UNIDA Gontor telah melakukan marketing public relations dalam meningkatkan penghimpunan dana dari teori marketing public relations yang dikemukakan oleh Thomas L. Harris yaitu three ways strategy: push, pull dan pass. Push strategy LAZISWAF UNIDA Gontor melakukan donasi secara door to door keliling asrama mahasiswa, daur jabi keliling kerumah dosen, menyebarkan poster one day one story ke grup-grup mahasiswa melalui whatsapp dan instagram. Pull strategy LAZISWAF UNIDA Gontor melakukan periklanan berupa bulletin dan poster, serta melalui baliho, dan melakukan publikasi di media sosial seperti Instagram, Youtube, dan website. Pass strategy LAZISWAF UNIDA Gontor melakukan program sosial seperti: wakaf Al-Qur’an, UNIDA peduli bencana alam, dan Kajian Zakat dan Wakaf. Implikasi dari temuan ini adalah bahwa strategi PR yang menyeluruh, menggabungkan pendekatan push, pull, dan pass, dapat secara signifikan meningkatkan upaya penggalangan dana selama berbagai periode.